Pengelolaan Sistem Informasi Desa (SID) Menggunakan Open SID di PEMDES Cisumur - Dina Merlinda Izzah (Jurnal Teknologi dan Bisnis, 2022)
Information and Communication Technology (ICT) is one of the determinants of village development. The presence of ICT is an enabling condition to accelerate the development process in rural areas. This study aimed to analyze the use of village websites for development based on the perspective of Actor-Network Theory in Cisumur Village, Gandrungmangu District, Cilacap Regency, Jawa Tengah Province. The method used in this research is qualitative with case studies. Data were collected by in-depth interviews, observation, and documentation. The technique of determining informants is done with a snowball (snowball). The results show that the use of village websites involves actors, and it occurs through translation which consists of several stages. The first is a problematization stage beginning with complaints and the village head’s desire to open access to public information. The next stage, interest, is when the Head of Finance, ICT Volunteers, Jawa Tengah Journalists, and local village assistants support the expectations of the village head. The enrolment stage is a division of roles in making the website so that it is connected to the Open SID community. Lastly, mobilization, it is when Cisumur.id has been used as the official website of the Cisumur Village. Based on the translation process, the actors involved are classified according to their interests and influences, consisting of key players, subjects, context setters, and crowd. The effect of using village websites is to open access to village information, manage village data well to be more transparent, help communities promote local products, and get various awards